Medical teachers in the 21st Century: reflections from Paulo Freire and Theodor Adorno - Cosme Gutierrez Duran, Cinthya; Mahfuz Daud Gallotti, Renata; Lopes Calvo Tibério, Iolanda de Fátima; Ferreira Mafra, Jason (O Mundo da Saúde, 2013)
Contemporary society needs competent, humane, doctors able to solve problems in the most varied contexts. This implies to look for new pedagogic approaches that value integrated teaching, the active participation of pupils in the process of apprenticeship, diversification of teaching settings situations, and early insertion of pupils in practical activities. Real experiences need to be built and lived by students for reflection, understanding and proposition of solutions. In this work we discuss the role of medical teachers as agents of transformation and education, using as theoretical reference systems those by Paulo Freire and Theodor Adorno.